2011
DOI: 10.4236/ojog.2011.14038
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of a recurrent puerperal uterine inversion with bakri<sup>®</sup> balloon tamponade

Abstract: Puerperal Uterine Inversion (PUI) is a rare but potentially life-threatening delivery complication in which the uterine fundus collapses within the endometrial cavity. This "glove-finger" introflexion of uterine walls generally occurs as an immediate postpartum complication and is responsible of different degrees of vaginal bleeding, shock and hypogastric pain that can cause serious maternal complications, including death. There are few reports of recurrent postpartum uterine inversion like the one we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In 2009, Soleymani MH et al have reported first successful management of recurrent uterine inversion with Surgical Obstetric Silicone bakri balloon; then by Elósegui JJH et al in 2011. 3,4 Kabir N et al and Sharma N et al have reported acute uterine inversion managed by Johnson's maneuver; then subacute uterine inversion by Haultain's operation (cervical ring is posteriorly incised to facilitate uterine replacement by Huntington method). 5,6 Another case report of successful management of recurrent puerperal uterine inversion was managed first by Jhonson's maneuver for acute inversion and for recurrent uterine inversion exploratory laparotomy was done to reposit by Huntington technique (progressive upward traction on each round ligament by application of atraumatic clamps with simultaneous upward pressure transvaginally) and multiple Cho suture; bilateral uterine arteries and utero ovarian arteries were ligated prophylactically.…”
Section: Commentsmentioning
confidence: 99%
“…In 2009, Soleymani MH et al have reported first successful management of recurrent uterine inversion with Surgical Obstetric Silicone bakri balloon; then by Elósegui JJH et al in 2011. 3,4 Kabir N et al and Sharma N et al have reported acute uterine inversion managed by Johnson's maneuver; then subacute uterine inversion by Haultain's operation (cervical ring is posteriorly incised to facilitate uterine replacement by Huntington method). 5,6 Another case report of successful management of recurrent puerperal uterine inversion was managed first by Jhonson's maneuver for acute inversion and for recurrent uterine inversion exploratory laparotomy was done to reposit by Huntington technique (progressive upward traction on each round ligament by application of atraumatic clamps with simultaneous upward pressure transvaginally) and multiple Cho suture; bilateral uterine arteries and utero ovarian arteries were ligated prophylactically.…”
Section: Commentsmentioning
confidence: 99%